TINGKAT EFEKTIVITAS SISTEM PERINGTAN DINI BANJIR LAHAR HUJAN DI KALI PUTIH KABUPATEN MAGELANG - , SURYA HEPPY KURNIASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The effectiveness measurement of lahar early warning system, need to be done to ensure systemâs goal which is to improve community preparedness so that damage and losses caused by lahar disaster can be minimized. The purpose of this study is to determine the effectiveness level of early warning system in response to lahar in Kali Putih, Magelang regency. Variables used in this study consisted early warning system administrator, which is government and society as a user. Primary data were obtained through questionnaires from 171 administrators respondent and 279 users respondent. Data analysed using statistical test, data normality test using Kolmogorov-Smirnov, system effectiveness level test using non parametric statistic Mann-Whitneyâs 2-independent samples, and to know factors affecting efectiveness level using Linier Regression. Analysis result shows that the goal composed by early warning systemâs administrator is not suitable with the output that systemâs users. That means the goal composed by administrator to warn the public against disaster was not delivered, based on Linier Regression analysis result, it can be concluded that there are three factors that affect ineffectiveness level of cold lava flood early warning system, such as prediction, interpertation, and response. It is supported by socialization cluster, infrastructures and quality of human resources. Early warning system should be equipped with automatic notification tool and adapt with culture of the society.